2012
DOI: 10.3109/10837450.2012.710240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different polymers and their combinations on the release of metoclopramide HCl from sustained-release hydrophilic matrix tablets

Abstract: Metoclopramide HCl (MTC) is commonly used for the management of gastrointestinal disorders. It has a short biological half-life and is usually administered four times daily to maintain effective concentrations throughout the day. The aim of this study is to develop sustained-release hydrophilic matrix tablet formulations of drug to achieve reproducible and predictable release rates, extended duration of activity, decreased toxicity, reduction of required dose, optimized therapy, and improved patient compliance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…HPMC is the most popular hydrophilic matrix former for production of controlled release tablets as it is non-ionic, stable over a broad pH range, enzyme resistant, odourless and tasteless, extensively studied and understood, non-toxic and costeffective [4][5][6][7][8]. Moreover the available variety of HPMC grades with different substitution degrees and viscosities make it a versatile matrix former for controlled release of a wide range of drugs with varying solubilities and doses [8].…”
Section: Introductionmentioning
confidence: 99%
“…HPMC is the most popular hydrophilic matrix former for production of controlled release tablets as it is non-ionic, stable over a broad pH range, enzyme resistant, odourless and tasteless, extensively studied and understood, non-toxic and costeffective [4][5][6][7][8]. Moreover the available variety of HPMC grades with different substitution degrees and viscosities make it a versatile matrix former for controlled release of a wide range of drugs with varying solubilities and doses [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxypropyl methylcellulose (HPMC) is the most commonly used hydrophilic matrix in the pharmaceutical industry owing to its nonionicity, nontoxicity, stability in different pH solutions, and cost-effectiveness. 6 To find out the DMAs of HPMC, many previous studies have examined the chemical, 7 mechanical, 8 and thermal 9 properties of HPMC, as well as the effects of viscosity, particle size, and other properties on drug release. 10 Recent types of research have investigated the relationship between the HPMC properties and the drug dissolution by using various new characterization methods, such as modulated differential scanning calorimetry (DSC) 11 nuclear magnetic resonance, 12 FTIR, 13 and statistical methods.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It shows a good stability in acidic and alkaline medium but has a short half-life of 3-5 hours. 1,5 MH is usually given at a dose of 10-15 mg for four times a day to maintain the effective blood concentration. It has been suggested that a sustained release (SR) preparation of MH designing for twice daily administration might be an advantageous dosage form, especially in long term therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a sustained release (SR) preparation of MH designing for twice daily administration might be an advantageous dosage form, especially in long term therapy. [3][4][5][6] Correspondence to: Syed Shabbir Haider Email: haidersyedshabbir@yahoo.com Dhaka Univ. J. Pharm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation